Implementasi Just-In-Time Dalam Usaha Kecil Menengah (Studi Kasus Keripik Pisang Bunda) - Finky Damayanti; Purwanti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Implementation Just-In-Time (JIT) in Small and Medium Enterprises (SMEs) is a management strategy that aims to minimize waste and increase operational efficiency. JIT focuses on managing the timing and quantity of arrival of raw materials to match production needs, thereby reducing storage costs and increasing responsiveness to market demand. This research was conducted on MSMEs producing banana chips in Bekasi Regency, using a qualitative descriptive approach to identify the practices, benefits and challenges of implementing JIT. The research results show that implementing JIT has succeeded in reducing storage costs, increasing production response time, and increasing customer satisfaction. However, challenges such as dependence on suppliers and limited resources are also faced. The conclusion of this research emphasizes the importance of mitigation strategies to overcome these challenges so that SMEs can utilize JIT optimally in increasing competitiveness in the market.